2022
DOI: 10.3390/gels9010032
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Ivory Nut Residue Valorization as a Source of Nanocellulose Colloidal Suspensions

Abstract: Ivory nut seeds have been traditionally exploited in Central and South America for obtaining vegetable ivory. The residues from this industry are susceptible to valorization as a source of fatty acids (by organic extraction) and mannans (by alkaline dissolution and regeneration). Nonetheless, cellulose may also be recovered at the end of this fractionation process by acid hydrolysis and functionalization, with associated advantages over other lignocellulosic sources due to the absence of lignin in the endosper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Carvajal-Barriga et al (2022) used the sulfuric acid hydrolysis method followed by ultrasonication to produce nanocellulose from ivory seeds. They reported that stable nanocellulose gel (1% solid content) could be obtained after 4 h of hydrolysis at 60 °C using 8 M H2SO4 (Carvajal-Barriga et al 2022). Another example, using green vegetable waste such as lettuce, leek, and artichokes as feedstocks, was demonstrated by Sanchez-Salvador et al (2022b).…”
Section: Overview Of Agricultural Residues and Natural Fibers For Nan...mentioning
confidence: 99%
“…Carvajal-Barriga et al (2022) used the sulfuric acid hydrolysis method followed by ultrasonication to produce nanocellulose from ivory seeds. They reported that stable nanocellulose gel (1% solid content) could be obtained after 4 h of hydrolysis at 60 °C using 8 M H2SO4 (Carvajal-Barriga et al 2022). Another example, using green vegetable waste such as lettuce, leek, and artichokes as feedstocks, was demonstrated by Sanchez-Salvador et al (2022b).…”
Section: Overview Of Agricultural Residues and Natural Fibers For Nan...mentioning
confidence: 99%
“…[11] As a subtractive manufacturing process, the production of vegetable ivory ornaments produces a powder residue which may correspond from 65% to 88% of the original material. [12] These particles have no current valorization strategy and are a potential source of mannan, nanocellulose, and pyrolysis products [9,12,13] owing to their high carbohydrate content (ca. 70 wt% homomannan and 7.5 wt% cellulose).…”
mentioning
confidence: 99%